Teacher cognition in language teaching - Woods, Devon (Cambridge Univ. Press, 1996)
The book is a examination of how and what teachers think in their practice of language teaching. Based on case study of university level ESL teachers in Canada, it looks at the planning practices of teachers, both in preparation for the classroom and during the moment-to moment decision-making that occurs in the classroom. It also looks at how teachers interpret and evaluate the events, activities and interactions that occur in the teacher process, and how these interpretation and evaluation feed back into subsequent planning. It examines the structure of teachers' belief, assumptions and background knowledge and elaborates on the role that these play in the decision-making process